2019
DOI: 10.3748/wjg.v25.i22.2809
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis treatment in the elderly: A systematic review

Abstract: BACKGROUND Autoimmune hepatitis (AIH) is a rare chronic inflammatory liver disease with a high risk of progression to liver cirrhosis. The initial treatment for AIH usually includes a steroid, with or without azathioprine. AIH can present at any age; however, the most effective and safe induction treatment for AIH in the elderly remains unclear. AIM To systematically review available data on both effectiveness and safety of AIH treatments in elderly subjects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…However, the response rates as shown by our study suggest that even AIH patients ≥70 y can be candidates for immunosuppression. In this context, a recent meta‐analysis showed that standard therapy was effective in inducing remission in the older, while treatment failure and relapses were less often compared to younger patients 15 . Our results further support the existing data, although it should be emphasized that this is the first report specifically designed in AIH patients ≥70 y who were treated with prednisolone and MMF as front‐line therapy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, the response rates as shown by our study suggest that even AIH patients ≥70 y can be candidates for immunosuppression. In this context, a recent meta‐analysis showed that standard therapy was effective in inducing remission in the older, while treatment failure and relapses were less often compared to younger patients 15 . Our results further support the existing data, although it should be emphasized that this is the first report specifically designed in AIH patients ≥70 y who were treated with prednisolone and MMF as front‐line therapy.…”
Section: Discussionsupporting
confidence: 86%
“…Another relevant question is the issue of treatment, with controversy regarding benefits in this group of patients 10,11,15,29,31 . Treating aged with high doses or lengthy intervals of immunosuppression remains a matter of concern for many physicians which is not sufficiently addressed so far, as patients aged ≥70 y are often excluded from trials 15,29 . From a clinical point of view, most hepatologists, internists and general practitioners will be reluctant to administer corticosteroids to older patients, especially when comorbidities such as osteopenia or diabetes and polypharmacy may be present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, AIH diagnosed in the elderly is characterized by more asymptomatic cases, more often delayed diagnosis, and higher rates of comorbidity, cirrhosis, and extrahepatic diseases, such as thyroid or rheumatic disease [ 60 , 314 - 316 ]. Elderly patients respond well to the immunosuppressive therapy, with less relapse after treatment withdrawal [ 317 , 318 ]. However, the cut-off age to define the elderly population varies from 60 to 70 years in each study, and some studies have reported no difference in clinical features and treatment responses according to age [ 315 , 319 ].…”
Section: Treatmentmentioning
confidence: 99%
“…60,[314][315][316] Elderly patients respond well to the immunosuppressive therapy, with less relapse after treatment withdrawal. 317,318 However, the cut-off age to define the elderly population varies from 60 to 70 years in each study, and some studies have reported no difference in clinical features and treatment responses according to age. 315,319 In elderly patients, drug use to control other comorbidities is common.…”
Section: Old Agementioning
confidence: 99%